Structure of SARS-CoV-2 - International Livestock Research Institute (International Livestock Research Institute, 2020)
What does the COVID-19 virus look like? What is it made out of? A short animated explainer produced for the joint International Livestock Research Institute and United Nations Environmental Programme #ZoonosesReport - 'Preventing the pandemic: zoonotic diseases and how to break the chain of transmission' To learn more and download the report, visit ilri.org/preventing-next-pandemic Virus model and animation produced by Annabel Slater.